Protective Effects of Broussonetia kazinoki Siebold Fruit Extract against Palmitate-Induced Lipotoxicity in Mesangial Cells. (8th January 2019) - Kim, Donghee; Kim, Hyo-Jin; Cha, Seon-Heui; Jun, Hee-Sook
Abstract : Diabetic nephropathy is one of the most serious complications of diabetes. Lipotoxicity in glomerular mesangial cells is associated with the progression of diabetic nephropathy. Paper mulberry, Broussonetia kazinoki Siebold (BK), has been used in oriental medicine for human health problems. However, to date, the beneficial effect of BK fruit has not been studied. In this study, we investigated the protective effect of an ethanolic extract of BK fruit (BKFE) against palmitate- (PA-) induced toxicity in mesangial cells. BKFE significantly increased the viability of PA-treated SV40 MES13 cells. BKFE significantly inhibited PA-induced apoptosis and decreased the expression of apoptotic genes, cleaved caspase-3, and cleaved PARP. Moreover, BKFE inhibited the expression of endoplasmic reticulum (ER) stress-related genes, such as BiP, phosphorylated eIF2 α, cleaved ATF6, and spliced XBP-1, in PA-treated SV40 MES13 cells. BKFE decreased PA-induced ROS production. In addition, BKFE activated the transcription factor Nrf2 and increased the expression of antioxidant enzymes. However, knockdown of Nrf2 using siRNA suppressed this BKFE-induced increase in antioxidant enzyme expression. Furthermore, the protective effect of BKFE on PA-induced apoptosis was significantly reduced by Nrf2 knockdown. In conclusion, BKFE induced the expression of antioxidant enzymes via activation of Nrf2 and protected against PA-induced lipotoxicity in mesangial cells.